Global perspectives of the bulk electronic structure of URu2Si2 from angle-resolved photoemission. (1st January 2022) - Denlinger, J D; Kang, J-S; Dudy, L; Allen, J W; Kim, Kyoo; Shim, J-H; Haule, K; Sarrao, J L; Butch, N P; Maple, M B
Abstract: Previous high-resolution angle-resolved photoemission (ARPES) studies of URu2 Si2 have characterized the temperature-dependent behavior of narrow-band states close to the Fermi level ( E F ) at low photon energies near the zone center, with an emphasis on electronic reconstruction due to Brillouin zone folding. A substantial challenge to a proper description is that these states interact with other hole-band states that are generally absent from bulk-sensitive soft x-ray ARPES measurements. Here we provide a more global k -space context for the presence of such states and their relation to the bulk Fermi surface (FS) topology using synchrotron-based wide-angle and photon energy-dependent ARPES mapping of the electronic structure using photon energies intermediate between the low-energy regime and the high-energy soft x-ray regime. Small-spot spatial dependence, f -resonant photoemission, Si 2 p core-levels, x-ray polarization, surface-dosing modification, and theoretical surface slab calculations are employed to assist identification of bulk versus surface state character of the E F -crossing bands and their relation to specific U- or Si-terminations of the cleaved surface. The bulk FS topology is critically compared to density functional theory (DFT) and to dynamical mean field theory calculations. In addition to clarifying some aspects of the previously measured high symmetry Γ, Z and X points, incommensurate 0.6 a * nested Fermi-edge states located along Z – N – Z are found to be distinctly different from the DFT FS prediction. The temperature evolution of these states above T HO, combined with a more detailed theoretical investigation of this region, suggests a key role of the N -point in the hidden order transition.